Bone retouchers from Lower Palaeolithic sites: Terra Amata, Orgnac 3, Cagny-l'Epinette and Cueva del Angel. (21st July 2016) - Moigne, Anne-Marie; Valensi, Patricia; Auguste, Patrick; García-Solano, José; Tuffreau, Alain; Lamotte, Agnès; Barroso, Cecilio; Moncel, Marie-Hélène
Abstract: Bone retouchers are more common during the Middle Palaeolithic (from MIS 7 to 3) and are now considered as a part of the tool kit of Neanderthals. In Middle Pleistocene and Lower Palaeolithic assemblages, they are few in number and attest to the scarcity of use of bones as material for shaping tools. Some MIS 11 to MIS 9 sites allow the description of the onset of bone use and its multiplication after the MIS 9 attests of another functional relationship between bones and hominins. Our aim is to provide details about the bone retouchers found in some MIS 11–9 sites with lithic assemblages, often described as late Acheulean, that include handaxes and heavy-duty tools. The sites sampled are Terra Amata (south-east France, MIS 11), Orgnac 3 (south-east France, MIS 9–8), Cagny l'Epinette (Northern France, MIS 9) and Cueva del Angel (Spain, MIS 11–7). The study examined the number of retouchers, their support and type of animal, types of marks, bone sizes, and the lithic and faunal contexts. While bone retouchers sometimes total several hundreds of pieces in Middle Palaeolithic sites, our Lower Palaeolithic corpus yields generally between 1 and 6 retouchers. Retouchers are always made on fragments of bones from the main hunted species (horses, large bovids and cervids). Marks on bone retouchers indicate specific processes for selecting fragments of bones, and hypotheses are provided on their method of use. Categories may be suggested according to their types of support (diaphysis, epiphysis) as well as their types of marks, and allow us to suggest hypotheses for the retouching of both bifacial tools and flake-tools as well as for direct percussion. The results are compared with other sites from which bone retouchers were already published (Cueva del Bolomor, Gran Dolina TD10 in Spain, and La Micoque in France and Qesem in Israel). They are also compared with younger Acheulean assemblages such as Lazaret cave in France.